2008
DOI: 10.1016/j.psychsport.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of behavior change in two tailored physical activity interventions for adolescent girls

Abstract: Participation in regular physical activity is associated with a variety of positive outcomes for young people (Strong et al., 2005). Although many of the physiological benefits of physical activity are difficult to establish during youth (Cavill, Biddle, & Sallis, 2001; Riddoch, 1998), longitudinal studies have consistently demonstrated a positive link between an active lifestyle and a number of favorable outcomes during this period (Boreham et al., 2004; Epstein, Paluch, Gordy, & Dorn, 2000; McMurray et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
3
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 46 publications
6
87
3
5
Order By: Relevance
“…However, the prevalence of inactivity among Taiwan college students has increased for the last decade; there are only 10.7% who exercise regularly enough to the recommended level that can reap the health benefits (Lin et al 2006), thus, those inactive may lead to adverse health consequences early in life (Racette et al 2007). While Taymoori and Lubans (2008) suggested that the lack of knowledge regarding the mechanisms responsible for behavior change may explain the low levels of effectiveness in PA interventions among individuals, Dishman (2004) indicated that emotional changes related to exercise are an important part of exercise adherence. Thus, hypothesizing EI as a key component for the development of regular exercise behavior seems rationale.…”
Section: Does Emotional Intelligence Lead To Changes In Exercise Behamentioning
confidence: 99%
“…However, the prevalence of inactivity among Taiwan college students has increased for the last decade; there are only 10.7% who exercise regularly enough to the recommended level that can reap the health benefits (Lin et al 2006), thus, those inactive may lead to adverse health consequences early in life (Racette et al 2007). While Taymoori and Lubans (2008) suggested that the lack of knowledge regarding the mechanisms responsible for behavior change may explain the low levels of effectiveness in PA interventions among individuals, Dishman (2004) indicated that emotional changes related to exercise are an important part of exercise adherence. Thus, hypothesizing EI as a key component for the development of regular exercise behavior seems rationale.…”
Section: Does Emotional Intelligence Lead To Changes In Exercise Behamentioning
confidence: 99%
“…The majority of time that adolescent females are engaged in PA is during school and during the weekdays (Mota, Santos, Guerra, Ribeiro, & Duarte, 2003). PE class is effective at increasing moderate to vigorous activity among students and is an important avenue to provide adolescents with skills, knowledge, and capabilities to participate in PA for increased health benefits (Shen, McCaughtry, & Martin, 2007;Taymoori & Lubans, 2008). Not only do students learn the skills and knowledge to be healthy and active, they also learn how to live healthy lifestyles, as they become adults.…”
Section: Resultsmentioning
confidence: 99%
“…Many psychological benefits have been linked to PA including self-efficacy, self-esteem, and confidence. A study by Taymoori and Lubans (2008) found that adolescent girls who participated in a PA intervention had higher levels of self-efficacy and high levels of perceived benefits of PA when compared to girls who were not participating in the intervention. They also found that girls in the intervention group reported fewer barriers to being physically active.…”
Section: Discussionmentioning
confidence: 99%
“…Taymoori and Lubans 16 used theoretical constructs to aid the development of educational and counselling sessions for girls in order to identify potential mediators of PA behaviour change. Both interventions showed an intervention effect on self-reported PA.…”
Section: Interventions To Increase Girls' Physical Activitymentioning
confidence: 99%